Innovative Engine Prototype Powered by Diesel and LPG as Fuel for Agriculture - Siripornmongkolchai, Chaiyong (Journal of Advanced Development in Engineering and Science, 2023)
The objectives of this research were 1) to modify small engines for agriculture to be able to support both diesel and LPG fuel consumption in the form of using both types of fuel separately and 2) to compare diesel and LPG consumption rates by modifying a small diesel engine for agriculture, Yanmar TF120DI, and installing LPG fuel system, ignition system and an auxiliary combustion chamber place of the original diesel injectors. The auxiliary combustion chamber would reduce the compression ratio to accommodate LPG fuel, which was a characteristic of the gasoline engine. The auxiliary combustion chamber could be removed and then install a diesel injector to return using diesel fuel. From the test of using the power engine for pumping water with a Payanak pipe with the diameter of 8 inch at a constant engine speed of 1,000 rounds per minute, it was found that the average diesel usage was 0.92 kilograms per hour or 1.09 liters per hour with the cost of 28.35 baht per hour and if using LPG as fuel, average LPG was 0.53 kilograms per hour with the cost of 12.91 baht per hour, saving 54.46 percent of costs. However, when the engine runs as a diesel engine, it was found that black smoke was exhausted at 46.7 percent and 59.6 percent at 1,800 and 2,400 rounds per minute respectively. While running as a gasoline engine, it was found that the auxiliary combustion chamber temperature compared with the temperature of the engine cylinder head of Honda GX160 at maximum rounds per minute was 302 and 188 degrees Celsius, respectively, and found that the exhaust contained 0.69 percent carbon monoxide and 1,893 parts per million of hydrocarbons.